Climate-mediated behavioural variability in facultatively social bees. (24th July 2018) - Groom, Scott V C; Rehan, Sandra M
Abstract: Social organisms are some of the most pervasive on earth, with the origin of sociality considered a major evolutionary transition. Previous studies suggest a role for both genetic and environmental factors in the transition from solitary to social living, with the relative contributions of these factors varying among taxa. Eusociality has arisen up to 11 times in the Hymenoptera. Four of these origins occurred within the bees, plus many probable reversions, making them ideal to understand the influence of genes and environment on social behaviour. We used a well-supported phylogeny with broad taxonomic coverage of the globally distributed bee genus Ceratina to test whether climate and sociality are correlated. Ceratina was most probably social ancestrally and originated in tropical Africa, with subsequent dispersals into temperate regions corresponding to shifts to solitary living. These findings highlight the utility of facultatively social lineages, such as Ceratina, for assessing the relative importance of phylogeny and ecology in the evolution of social complexity.